FACTORS OF PROBLEMS INDONESIA TO EXPORT ARECA NUT TO SINGAPORE CASE STUDY : JAMBI - Pratiwi, Fadilla Resti Kurnia; Yealta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is a study of the constraints of Indonesian areca nut exports to Singapore with the Jambi case study in 2013-2018. This study aims to explain the causes of the problem of areca nut exports to Singapore. This has caused the export of areca nut to decline. This research was developed based on the framework of a neomerkantilism perspective which is supported by the theory of international trade, and also the level of analysis that uses a nation state. In accordance with the fact that the main object of international relations is the nation-state. And the theory used in this study is the theory of international trade. This study uses field research methods and research and literature. The export constraint factors are the decline in the quality and quantity of betel nuts is the government's efforts have not been optimal in overseeing agricultural production, lack of effectiveness of export promotions at international exhibitions, speculators monopoly, government control of illegal trade / smuggling, the export chain of betel nut infrastructure , the role of exporter companies has not been maximized due to unclear regulations.Key words: Areca nut, Perspective of neomerkantilism, International Trade